2020
DOI: 10.1177/0260107920935726
|View full text |Cite
|
Sign up to set email alerts
|

Conflict–Poverty Relationship in Africa: A Disaggregated Approach

Abstract: This article investigates the conflict–poverty relationship in Africa between 1980 and 2015. Conducting a panel regression, we test the effect of disaggregated conflict on the poverty index (POV) and indicators in Africa. Conflict causes poverty in Africa, and not the other way round as many studies have suggested. We also found that internal conflict causes poverty in Africa; it increases the poverty rate and worsens the standard of living. However, interstate conflicts have little effects on poverty indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…For example, because of crowding and poor access to WASH, poor urban settlements have faced the brunt of outbreaks, including Zika infection, Ebola virus disease, typhoid, and cholera ( 45 ). Conflict can result in loss of possessions, loss of habitual residence, and an inability to find employment, thereby reducing income generation, savings, and financial backstops ( 13 ). In times of worsening poverty, persons may not be able to afford healthcare and basic medical supplies, especially those in vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, because of crowding and poor access to WASH, poor urban settlements have faced the brunt of outbreaks, including Zika infection, Ebola virus disease, typhoid, and cholera ( 45 ). Conflict can result in loss of possessions, loss of habitual residence, and an inability to find employment, thereby reducing income generation, savings, and financial backstops ( 13 ). In times of worsening poverty, persons may not be able to afford healthcare and basic medical supplies, especially those in vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during the 2018 Ebola outbreak in DRC, healthcare facilities were attacked, dampening efforts to control the virus ( 12 ). Conflict can worsen preexisting vulnerabilities, including poverty, because conflicts can cause loss of income, disruption to education, damage to livelihoods, and displacement ( 13 ).…”
mentioning
confidence: 99%
“…For example, poor urban settlements have faced the brunt of outbreaks including Zika, Ebola, typhoid, and cholera, due to crowding and poor access to WASH ( 45 ). Conflict can result in loss of possessions, habitual residence, and an inability to find employment, reducing income generation, savings and financial backstops ( 13 ). In times of worsening poverty, people may not be able to afford healthcare and basic medical supplies, especially in vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during the 2018 Ebola outbreak in the DRC healthcare facilities were attacked, dampening efforts to control the virus ( 16 ). Conflict can worsen pre-existing vulnerabilities including poverty, as conflicts can cause loss of income, disruption to education, damage to livelihoods and displacement ( 17 ).…”
mentioning
confidence: 99%
“…Disruptions like political instability, natural disaster, pandemics, or conflicts have significant detrimental impacts on social, economic, and human development (Von Einsiedel et al 2017;Schillinger et al 2020;Qayyum, Anjum, and Sabir 2021;Menton et al 2021;Hamoodi 2021;Okunlola and Okafor 2020;. These disruptions also challenge the United Nations' Sustainable Development Goals regarding "No poverty (goal 1)," "Zero hunger (goal 2)," "Good health and well-being (goal 3)," "Responsible consumption and production (goal 12)," and "Peace, justice, and strong institutions (goal 16)," For example, revealed that armed conflicts (Fulani ethnic militia) in Nigeria negatively affected farm outputs, areas harvested, and cattle holding.…”
Section: Introductionmentioning
confidence: 99%